High-plasticity high-temperature-resistant high-entropy alloy and preparation method thereof

By introducing V and B elements into CoCrFeNi high-entropy alloy, the Cr2B phase is formed, the strength and hardness of the alloy are improved, and the performance is stable at high temperatures, which solves the problem of safety hazards in power grid bolts and achieves high strength and high temperature stability high entropy alloy application.

CN119177390APending Publication Date: 2024-12-24ELECTRIC POWER RESEARCH INSTITUTE OF STATE GRID SHANDONG ELECTRIC POWER COMPANY +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411373084.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

In engineering applications, the existing CoCrFeNi high-entropy alloys often have cracks, fractures and other defects during the operation of power grid bolts, which bring safety hazards.

Method used

V and B elements are introduced into the CoCrFeNi matrix, and the Cr2B phase is formed through solid solution strengthening and second phase strengthening, which improves the strength and hardness of the alloy, and maintains the structure and performance stable at high temperatures.

Benefits of technology

It realizes the high strength, excellent strong plasticity and good high temperature stability of CoCrVxFeNiBy high-entropy alloy, and is suitable for the preparation of power grid bolt components and solves safety hazards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119177390A_ABST
    Figure CN119177390A_ABST
Patent Text Reader

Abstract

The high-plasticity high-temperature-resistant high-entropy alloy is composed of Co, Cr, V, Fe, Ni and B, the element composition is CoCrVxFeNiBy, x is larger than or equal to 0.1 and smaller than or equal to 1, and y is larger than or equal to 0.1 and smaller than or equal to 1. The preparation method comprises the following steps: (1) weighing and mixing a Co raw material, a Cr raw material, a V raw material, a Fe raw material, a Ni raw material and a B raw material according to a target molar ratio, and (2) putting the mixture obtained in the step (1) into a medium-frequency induction furnace for smelting, and pouring the mixture into a crucible for cooling and solidification after uniformly melting. The high-entropy alloy provided by the invention not only has good mechanical properties, excellent strength and plasticity matching and high strength, but also has good high-temperature stability, and can be used for preparing power grid bolt parts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of high entropy alloys, and more particularly to a high-plasticity, high-temperature-resistant high entropy alloy and a preparation method thereof. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] High entropy alloys are a new type of multi-principal alloy that has been rapidly developed in the past decade and has subverted the traditional alloy design concept. They break the traditional alloy mode of mainly using one or two metal elements and obtaining different properties by adding a small amount of specific other elements. Instead, they are made of four or more main elements mixed in an equiatomic ratio or a near-equiatomic ratio. Therefore, they can have many unique and excellent performance characteristics, such as high hardness, high strength, high temperature stability, wear resistance, corrosion resistance, etc. CoCrFeNi alloy has attracted widespread attention due to its excellent plasticity and is currently the most studied high entropy alloy, but its engineering application is limited due to problems such as low strength, poor hardness and wear resistance.

[0004] Bolts, as a key connection part, are widely used in the engineering field. However, due to problems with their own structure and process, they often produce cracks, fractures and other defects due to the dual effects of performance and environment during operation, bringing major safety hazards.

[0005] Therefore, it is necessary to develop a new type of high-entropy alloy with strong plasticity, high strength and high temperature resistance, which can be applied to power grid bolt components to solve the safety problems caused by the operation of power grid bolts. Summary of the invention

[0006] In order to solve the deficiencies of the prior art, the present invention provides a high-entropy alloy with strong plasticity and high temperature resistance and a preparation method thereof.

[0007] The technical solution adopted by the present invention is as follows:

[0008] In a first aspect of the present invention, a high-entropy alloy with strong plasticity and high temperature resistance is provided, which is composed of Co, Cr, V, Fe, Ni and B, and the element composition is CoCrV x FeNiB y , where 0.1≤x≤1, 0.1≤y≤1.

[0009] The CoCrV provided by the present invention x FeNiB yThe high entropy alloy introduces V and B elements into the CoCrFeNi matrix to improve the organizational structure of the matrix. The resulting solid solution strengthening and second phase strengthening effects greatly improve the strength of the alloy, showing a good match between strength and plasticity. At the same time, after high-temperature annealing, the organization and properties of the alloy do not change significantly, showing excellent high-temperature stability.

[0010] A second aspect of the present invention provides a method for preparing the high-ductility, high-temperature-resistant, high-entropy alloy as described in the first aspect, comprising:

[0011] (1) According to the target molar ratio, Co raw material, Cr raw material, V raw material, Fe raw material, Ni raw material and B raw material are weighed and mixed;

[0012] (2) The mixed material obtained in step (1) is placed in a medium frequency induction furnace for smelting, and after being evenly melted, poured into a crucible for cooling and solidification.

[0013] The preparation method provided by the invention is simple, highly practical, and easy to promote, and kilogram-level alloy ingots can be obtained.

[0014] In a third aspect, the present invention provides a high-strength, plastic, high-temperature-resistant, high-entropy alloy as described in the first aspect for application in power grid bolts.

[0015] In a fourth aspect, the present invention provides a high entropy alloy power grid bolt, which is made of the strong-plasticity, high-temperature-resistant high entropy alloy described in the first aspect.

[0016] One or more embodiments of the present invention have at least the following beneficial effects:

[0017] (1) The present invention uses a base alloy composed of Co, Cr, Fe, and Ni with a molar ratio of 1:1:1:1, and adds metal element V and non-metal element B for the first time, and further limits the stoichiometric ratio corresponding to V to 0.1≤x≤1, and the stoichiometric ratio corresponding to B to 0.1≤y≤1, so that the high entropy alloy described in the present application not only has good mechanical properties, excellent strength-plasticity matching and high strength, but also has good high-temperature stability, and can be used for the preparation of power grid bolt components.

[0018] (2) The present invention adopts the medium frequency induction furnace smelting method to realize the preparation of a new type of alloy ingot with uniform structure and stable performance. Kilogram-level alloy ingots are prepared, and the preparation method is simple, practical, and easy to promote. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0020] Figure 1X-ray diffraction patterns of the alloys prepared in Examples 1-4.

[0021] Figure 2 The compressive stress-strain curves of the alloys prepared in Examples 1-4.

[0022] Figure 3 These are SEM images of the alloys prepared in Examples 1-4, where (a) is Example 1, (b) is Example 2, (c) is Example 3, and (d) is Example 4.

[0023] Figure 4 Schematic diagram of the microhardness of the alloys prepared in Examples 1-4.

[0024] Figure 5 XRD patterns of the alloy prepared in Example 3 after annealing at 700°C and 900°C.

[0025] Figure 6 The tensile stress-strain curves of the alloy prepared in Example 3 after annealing at 700°C and 900°C. DETAILED DESCRIPTION

[0026] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0027] As mentioned above, it is necessary to develop a new type of high-entropy alloy with strong plasticity, high strength and high temperature resistance, which can be applied to power grid bolt components to solve the safety problems caused by the operation of power grid bolts.

[0028] In view of this, the present invention proposes a strong plasticity, high temperature resistant high entropy alloy, and provides a new design concept and preparation method of a strong plasticity, high temperature resistant high entropy alloy based on the development of the existing material system.

[0029] Specifically, in a typical embodiment of the present invention, a strong plastic high temperature resistant high entropy alloy is provided, which is composed of Co, Cr, V, Fe, Ni and B, and the element composition is CoCrV x FeNiB y , where 0.1≤x≤1, 0.1≤y≤1.

[0030] The CoCrV provided by the present invention x FeNiB yThe high entropy alloy introduces V and B elements into the CoCrFeNi matrix to improve the organizational structure of the matrix. The resulting solid solution strengthening and second phase strengthening effects greatly improve the strength of the alloy, showing a good match between strength and plasticity. At the same time, after high-temperature annealing, the organization and properties of the alloy do not change significantly, showing excellent high-temperature stability.

[0031] The addition of V and B elements can change the microstructure and mechanical properties of CoCrFeNi high entropy alloy. CoCrFeNi high entropy alloy is a single FCC phase. After adding V and B elements, a large amount of hard and brittle Cr2B phase is precipitated, which greatly improves the strength and hardness. x FeNiB y High entropy alloys show good strength-ductility matching. At the same time, CoCrV x FeNiB y The microstructure of the high entropy alloy has not changed and is still FCC+Cr2B phase, indicating that the alloy has good high temperature resistance.

[0032] In some embodiments, 0.1≤x≤0.5, 0.1≤y≤0.5; the strong plasticity, high temperature resistant high entropy alloy structure is composed of FCC phase and Cr2B phase, wherein the Cr2B phase content is ≥9.9%; the strong plasticity, high temperature resistant high entropy alloy has a tensile yield strength of ≥176.2MPa, a tensile strength of ≥390MPa, a tensile deformation rate of ≥1%, and a hardness of ≥165.4HV.

[0033] In another specific embodiment of the present invention, a method for preparing the above-mentioned strong plasticity high temperature resistant high entropy alloy is provided, comprising:

[0034] (1) According to the target molar ratio, Co raw material, Cr raw material, V raw material, Fe raw material, Ni raw material and B raw material are weighed and mixed;

[0035] (2) The mixed material obtained in step (1) is placed in a medium frequency induction furnace for smelting, and after being evenly melted, poured into a crucible for cooling and solidification.

[0036] The preparation method provided by the invention is simple, highly practical, and easy to promote, and kilogram-level alloy ingots can be obtained.

[0037] In some embodiments, the purity of the raw material in step (1) is ≥ 99.99 wt%.

[0038] In some embodiments, before the mixing in step (1), the Co raw material, Cr raw material, V raw material, Fe raw material, Ni raw material and B raw material are ultrasonically cleaned and dried to remove oil stains and impurities attached to the surface of the raw materials.

[0039] In some embodiments, the solvent for ultrasonic cleaning is anhydrous ethanol, and the time for ultrasonic cleaning is 6 to 8 minutes.

[0040] In some embodiments, in step (2), the medium frequency induction furnace is evacuated to 1-2×10 -3 Pa, then recoil argon to 0.06 ~ 0.08MPa, turn on the power, and then heat to 300 ℃, preheat for 5 ~ 8min, and then slowly heat until the raw material is completely melted after preheating, and keep warm for 10 ~ 15min.

[0041] In some embodiments, in step (2), the smelting current is 400-600A.

[0042] In another specific embodiment of the present invention, the present invention provides the above-mentioned strong plasticity, high temperature resistant and high entropy alloy for application in power grid bolts.

[0043] In another specific embodiment of the present invention, the present invention provides a high entropy alloy grid bolt, which is made of the above-mentioned strong plasticity and high temperature resistant high entropy alloy.

[0044] Example 1

[0045] This embodiment provides a high-entropy alloy with strong plasticity and high temperature resistance, the chemical formula of which is CoCrV 0.1 FeNiB 0.1 .

[0046] The CoCrV provided in this embodiment 0.1 FeNiB 0.1 The preparation method of the alloy comprises the following steps:

[0047] (1) According to the target molar ratio of Co:Cr:V:Fe:Ni:B=1:1:0.1:1:1:0.1, the mass ratios of Co raw material, Cr raw material, V raw material, Fe raw material, Ni raw material and B raw material are converted to the corresponding mass ratios, accurate to 0.001 g, and Co raw material, Cr raw material, V raw material, Fe raw material, Ni raw material and B raw material with a purity of more than 99.99wt.% are weighed and mixed;

[0048] Before mixing, the Co raw material, the Cr raw material, the V raw material, the Fe raw material, the Ni raw material and the B raw material are respectively ultrasonically cleaned with anhydrous ethanol for 6 to 8 minutes, and the cleaned raw materials are placed in a drying box and dried at 200° C. for 30 minutes;

[0049] (2) The mixed material obtained in step (1) is placed in a medium frequency induction furnace for smelting. Before smelting, the medium frequency induction furnace is evacuated to a vacuum of 1 to 2×10 -3Pa, then recoil argon to 0.06MPa, turn on the power, control the current during smelting to 420A, then heat up to 300℃, preheat for 5min, continue to increase the current after preheating and slowly heat until the raw material is completely melted, keep warm for 10min, then pour the molten alloy into a cooling crucible to obtain the CoCrV 0.1 FeNiB 0.1 High entropy alloy.

[0050] The CoCrV prepared in this example 0.1 FeNiB 0.1 X-ray diffraction patterns of high entropy alloys are shown in Figure 1 The compressive stress-strain curve is shown in Figure 2 As shown in the SEM images Figure 3 As shown, the microhardness is Figure 4 The hardness and strength test results are listed in Table 1.

[0051] Example 2

[0052] This embodiment provides a high-entropy alloy with strong plasticity and high temperature resistance, the chemical formula of which is CoCrV 0.5 FeNiB 0.1 .

[0053] The CoCrV provided in this embodiment 0.5 FeNiB 0.1 The preparation method of the alloy comprises the following steps:

[0054] (1) According to the target molar ratio of Co:Cr:V:Fe:Ni:B=1:1:0.5:1:1:0.1, the mass ratios of Co raw material, Cr raw material, V raw material, Fe raw material, Ni raw material and B raw material are converted to the nearest 0.001 g, and the Co raw material, Cr raw material, V raw material, Fe raw material, Ni raw material and B raw material with a purity of more than 99.99wt.% are weighed and mixed;

[0055] Before mixing, the Co raw material, the Cr raw material, the V raw material, the Fe raw material, the Ni raw material and the B raw material are respectively ultrasonically cleaned with anhydrous ethanol for 6 to 8 minutes, and the cleaned raw materials are placed in a drying box and dried at 200° C. for 30 minutes;

[0056] (2) The mixed material obtained in step (1) is placed in a medium frequency induction furnace for smelting. Before smelting, the medium frequency induction furnace is evacuated to a vacuum of 1 to 2×10 -3 Pa, then backwash argon to 0.06MPa, turn on the power, control the current during smelting to 420A, then heat up to 300℃, preheat for 5min, continue to increase the current after preheating and slowly heat up until the raw material is completely melted, keep warm for 10min, and pour into the crucible after melting evenly to cool and solidify, to obtain the CoCrV0.5 FeNiB 0.1 High entropy alloy.

[0057] The CoCrV prepared in this example 0.5 FeNiB 0.1 X-ray diffraction patterns of high entropy alloys are shown in Figure 1 The compressive stress-strain curve is shown in Figure 2 As shown in the SEM images Figure 3 As shown, the microhardness is Figure 4 The hardness and strength test results are listed in Table 1.

[0058] Example 3

[0059] This embodiment provides a high-entropy alloy with strong plasticity and high temperature resistance, the chemical formula of which is CoCrV 0.5 FeNiB 0.3 .

[0060] The CoCrV provided in this embodiment 0.5 FeNiB 0.3 The preparation method of the alloy comprises the following steps:

[0061] (1) According to the target molar ratio of Co:Cr:V:Fe:Ni:B=1:1:0.5:1:1:0.3, the mass ratios of Co raw material, Cr raw material, V raw material, Fe raw material, Ni raw material and B raw material are converted to the nearest 0.001 g, and the Co raw material, Cr raw material, V raw material, Fe raw material, Ni raw material and B raw material with a purity of more than 99.99wt.% are weighed and mixed;

[0062] Before mixing, the Co raw material, the Cr raw material, the V raw material, the Fe raw material, the Ni raw material and the B raw material are respectively ultrasonically cleaned with anhydrous ethanol for 6 to 8 minutes, and the cleaned raw materials are placed in a drying box and dried at 200° C. for 30 minutes;

[0063] (2) The mixed material obtained in step (1) is placed in a medium frequency induction furnace for smelting. Before smelting, the medium frequency induction furnace is evacuated to a vacuum of 1 to 2×10 -3 Pa, then backwash argon to 0.06MPa, turn on the power, control the current during smelting to 420A, then heat up to 300℃, preheat for 5min, continue to increase the current after preheating and slowly heat up until the raw material is completely melted, keep warm for 10min, and pour into the crucible after melting evenly to cool and solidify, to obtain the CoCrV 0.5 FeNiB 0.3 High entropy alloy.

[0064] The CoCrV prepared in this example 0.5 FeNiB 0.3 X-ray diffraction patterns of high entropy alloys are shown in Figure 1 The compressive stress-strain curve is shown in Figure 2 As shown in the SEM images Figure 3 As shown, the microhardness is Figure 4 As shown in the figure, the XRD patterns after annealing at 700℃ and 900℃ are as follows Figure 5 As shown in the figure, the tensile stress-strain curves after annealing at 700℃ and 900℃ are as follows Figure 6 The hardness and strength test results are listed in Table 1.

[0065] Example 4

[0066] This embodiment provides a high-entropy alloy with strong plasticity and high temperature resistance, the chemical formula of which is CoCrV 0.5 FeNiB 0.5 .

[0067] The CoCrV provided in this embodiment 0.5 FeNiB 0.5 The preparation method of the alloy comprises the following steps:

[0068] (1) According to the target molar ratio of Co:Cr:V:Fe:Ni:B=1:1:0.5:1:1:0.5, the mass ratios of Co raw material, Cr raw material, V raw material, Fe raw material, Ni raw material and B raw material are converted to the nearest 0.001 g, and the Co raw material, Cr raw material, V raw material, Fe raw material, Ni raw material and B raw material with a purity of more than 99.99wt.% are weighed and mixed;

[0069] Before mixing, the Co raw material, the Cr raw material, the V raw material, the Fe raw material, the Ni raw material and the B raw material are respectively ultrasonically cleaned with anhydrous ethanol for 6 to 8 minutes, and the cleaned raw materials are placed in a drying box and dried at 200° C. for 30 minutes;

[0070] (2) The mixed material obtained in step (1) is placed in a medium frequency induction furnace for smelting. Before smelting, the medium frequency induction furnace is evacuated to a vacuum of 1 to 2×10 -3 Pa, then backwash argon to 0.06MPa, turn on the power, control the current during smelting to 420A, then heat up to 300℃, preheat for 5min, continue to increase the current after preheating and slowly heat up until the raw material is completely melted, keep warm for 10min, and pour into the crucible after melting evenly to cool and solidify, to obtain the CoCrV 0.5 FeNiB 0.5 High entropy alloy.

[0071] The CoCrV prepared in this example 0.5 FeNiB 0.5 X-ray diffraction patterns of high entropy alloys are shown in Figure 1 The compressive stress-strain curve is shown in Figure 2 As shown in the SEM images Figure 3 As shown, the microhardness is Figure 4 The hardness and strength test results are listed in Table 1.

[0072] Example 5

[0073] This embodiment provides a high-entropy alloy with strong plasticity and high temperature resistance, the chemical formula of which is CoCrV 0.5 FeNiB 0.7 .

[0074] The CoCrV provided in this embodiment 0.5 FeNiB 0.7 The preparation method of the alloy comprises the following steps:

[0075] (1) According to the target molar ratio of Co:Cr:V:Fe:Ni:B=1:1:0.5:1:1:0.7, the mass ratios of Co raw material, Cr raw material, V raw material, Fe raw material, Ni raw material and B raw material are converted to the nearest 0.001 g, and the Co raw material, Cr raw material, V raw material, Fe raw material, Ni raw material and B raw material with a purity of more than 99.99wt.% are weighed and mixed;

[0076] Before mixing, the Co raw material, the Cr raw material, the V raw material, the Fe raw material, the Ni raw material and the B raw material are respectively ultrasonically cleaned with anhydrous ethanol for 6 to 8 minutes, and the cleaned raw materials are placed in a drying box and dried at 200° C. for 30 minutes;

[0077] (2) The mixed material obtained in step (1) is placed in a medium frequency induction furnace for smelting. Before smelting, the medium frequency induction furnace is evacuated to a vacuum of 1 to 2×10 -3 Pa, then backwash argon to 0.06MPa, turn on the power, control the current during smelting to 420A, then heat up to 300℃, preheat for 5min, continue to increase the current after preheating and slowly heat up until the raw material is completely melted, keep warm for 10min, and pour into the crucible after melting evenly to cool and solidify, to obtain the CoCrV 0.5 FeNiB 0.7 High entropy alloy.

[0078] The CoCrV prepared in this example 0.5 FeNiB 0.7 The compressive stress-strain, hardness and strength test results of high entropy alloys are listed in Table 1.

[0079] Example 6

[0080] This embodiment provides a high-entropy alloy with strong plasticity and high temperature resistance, the chemical formula of which is CoCrV 0.5 FeNiB.

[0081] The CoCrV provided in this embodiment 0.5The preparation method of FeNiB alloy comprises the following steps:

[0082] (1) According to the target molar ratio of Co:Cr:V:Fe:Ni:B=1:1:0.5:1:1:1, the mass ratios of Co raw material, Cr raw material, V raw material, Fe raw material, Ni raw material and B raw material are converted to the nearest 0.001 g, and the Co raw material, Cr raw material, V raw material, Fe raw material, Ni raw material and B raw material with a purity of more than 99.99wt.% are weighed and mixed;

[0083] Before mixing, the Co raw material, the Cr raw material, the V raw material, the Fe raw material, the Ni raw material and the B raw material are respectively ultrasonically cleaned with anhydrous ethanol for 6 to 8 minutes, and the cleaned raw materials are placed in a drying box and dried at 200° C. for 30 minutes;

[0084] (2) The mixed material obtained in step (1) is placed in a medium frequency induction furnace for smelting. Before smelting, the medium frequency induction furnace is evacuated to a vacuum of 1 to 2×10 -3 Pa, then backwash argon to 0.06MPa, turn on the power, control the current during smelting to 420A, then heat up to 300℃, preheat for 5min, continue to increase the current after preheating and slowly heat up until the raw material is completely melted, keep warm for 10min, and pour into the crucible after melting evenly to cool and solidify, to obtain the CoCrV 0.5 FeNiB high entropy alloy.

[0085] The CoCrV prepared in this example 0.5 The compressive stress-strain, hardness and strength test results of FeNiB high entropy alloy are listed in Table 1.

[0086] Example 7

[0087] This embodiment provides a high-entropy alloy with strong plasticity and high temperature resistance, and the chemical formula is CoCrVFeNiB.

[0088] The preparation method of the CoCrVFeNiB alloy provided in this embodiment comprises the following steps:

[0089] (1) According to the target molar ratio of Co:Cr:V:Fe:Ni:B=1:1:1:1:1:1, the mass ratios of Co raw material, Cr raw material, V raw material, Fe raw material, Ni raw material and B raw material are converted to the nearest 0.001 g, and the Co raw material, Cr raw material, V raw material, Fe raw material, Ni raw material and B raw material with a purity of more than 99.99wt.% are weighed and mixed;

[0090] Before mixing, the Co raw material, the Cr raw material, the V raw material, the Fe raw material, the Ni raw material and the B raw material are respectively ultrasonically cleaned with anhydrous ethanol for 6 to 8 minutes, and the cleaned raw materials are placed in a drying box and dried at 200° C. for 30 minutes;

[0091] (2) The mixed material obtained in step (1) is placed in a medium frequency induction furnace for smelting. Before smelting, the medium frequency induction furnace is evacuated to a vacuum of 1 to 2×10 -3 Pa, then recoil argon to 0.06MPa, turn on the power, control the current during smelting to 420A, then raise the temperature to 300°C, preheat for 5 minutes, continue to increase the current after preheating and slowly raise the temperature until the raw material is completely melted, keep warm for 10 minutes, and after uniform melting, pour into a crucible to cool and solidify to obtain the CoCrVFeNiB high entropy alloy.

[0092] The compressive stress-strain, hardness and strength test results of the CoCrVFeNiB high entropy alloy prepared in this example are listed in Table 1.

[0093] Comparative Example 1

[0094] This comparative example provides a CoCrFeNi alloy, and the composition chemical formula of the CoCrFeNi alloy is CoCrFeNi.

[0095] The preparation method of the CoCrFeNi alloy provided in this comparative example comprises the following steps:

[0096] (1) According to the target molar ratio of Co:Cr:Fe:Ni=1:1:1:1, the mass ratios of Co raw material, Cr raw material, Fe raw material, and Ni raw material are converted to the nearest 0.001 g, and the Co raw material, Cr raw material, Fe raw material, and Ni raw material with a purity of more than 99.99 wt.% are weighed and mixed;

[0097] Before mixing, the Co raw material, the Cr raw material, the Fe raw material, and the Ni raw material are respectively ultrasonically cleaned with anhydrous ethanol for 6 to 8 minutes, and the cleaned raw materials are placed in a drying box and dried at 200° C. for 30 minutes;

[0098] (2) The mixed material obtained in step (1) is placed in a medium frequency induction furnace for smelting. Before smelting, the medium frequency induction furnace is evacuated to a vacuum of 1 to 2×10 -3 Pa, then recoil argon to 0.06MPa, turn on the power, control the current during smelting to 420A, then raise the temperature to 300°C, preheat for 5 minutes, continue to increase the current after preheating and slowly raise the temperature until the raw material is completely melted, keep warm for 10 minutes, and after uniform melting, pour into a crucible to cool and solidify to obtain the CoCrFeNi high entropy alloy.

[0099] That is, referring to Example 1, the difference of this comparative example is only that the V raw material and the B raw material are not added.

[0100] The compressive stress-strain, hardness and strength test results of the CoCrFeNi high entropy alloy prepared in this comparative example are listed in Table 1.

[0101] Comparative Example 2

[0102] This comparative example provides a high-entropy alloy with strong plasticity and high temperature resistance, the chemical formula of which is CoCrFeNiB 0.3 .

[0103] The CoCrFeNiB provided in this comparative example 0.3 The preparation method of the alloy comprises the following steps:

[0104] (1) According to the target molar ratio of Co:Cr:Fe:Ni:B=1:1:1:1:0.3, the mass ratios of Co raw material, Cr raw material, Fe raw material, Ni raw material and B raw material are converted to the nearest 0.001 g, and the Co raw material, Cr raw material, Fe raw material, Ni raw material and B raw material with a purity of more than 99.99wt.% are weighed and mixed;

[0105] Before mixing, the Co raw material, the Cr raw material, the Fe raw material, the Ni raw material and the B raw material are respectively ultrasonically cleaned with anhydrous ethanol for 6 to 8 minutes, and the cleaned raw materials are placed in a drying box and dried at 200° C. for 30 minutes;

[0106] (2) The mixed material obtained in step (1) is placed in a medium frequency induction furnace for smelting. Before smelting, the medium frequency induction furnace is evacuated to a vacuum of 1 to 2×10 -3 Pa, then backwash argon to 0.06MPa, turn on the power, control the current during smelting to 420A, then heat up to 300℃, preheat for 5min, continue to increase the current after preheating and slowly heat up until the raw material is completely melted, keep warm for 10min, and pour into the crucible after melting evenly to cool and solidify, to obtain the CoCrFeNiB 0.3 High entropy alloy.

[0107] That is, referring to Example 2, the difference of this comparative example is only that no V raw material is added.

[0108] The CoCrFeNiB prepared in this comparative example 0.3 The compressive stress-strain, hardness and strength test results of high entropy alloys are listed in Table 1.

[0109] Comparative Example 3

[0110] This comparative example provides a high-entropy alloy with strong plasticity and high temperature resistance, the chemical formula of which is CoCrV 0.5 FeNi.

[0111] The CoCrV provided in this comparative example 0.5 The preparation method of FeNi alloy comprises the following steps:

[0112] (1) According to the target molar ratio of Co:Cr:V:Fe:Ni:B=1:1:0.5:1:1:0.3, the mass ratios of Co raw material, Cr raw material, V raw material, Fe raw material and Ni raw material are converted to the nearest 0.001 g, and the Co raw material, Cr raw material, V raw material, Fe raw material and Ni raw material with a purity of more than 99.99wt.% are weighed and mixed;

[0113] Before mixing, the Co raw material, the Cr raw material, the V raw material, the Fe raw material and the Ni raw material are respectively ultrasonically cleaned with anhydrous ethanol for 6 to 8 minutes, and the cleaned raw materials are placed in a drying box and dried at 200° C. for 30 minutes;

[0114] (2) The mixed material obtained in step (1) is placed in a medium frequency induction furnace for smelting. Before smelting, the medium frequency induction furnace is evacuated to a vacuum of 1 to 2×10 -3 Pa, then backwash argon to 0.06MPa, turn on the power, control the current during smelting to 420A, then heat up to 300℃, preheat for 5min, continue to increase the current after preheating and slowly heat up until the raw material is completely melted, keep warm for 10min, and pour into the crucible after melting evenly to cool and solidify, to obtain the CoCrV 0.5 FeNi high entropy alloy.

[0115] That is to say, referring to Example 2, the difference of this comparative example is only that no B raw material is added.

[0116] The CoCrV prepared in this comparative example 0.5 The compressive stress-strain, hardness and strength test results of FeNi high entropy alloy are listed in Table 1.

[0117] Comparative Example 4

[0118] This comparative example provides a high-entropy alloy with strong plasticity and high temperature resistance, the chemical formula of which is CoCrV 1.5 FeNiB 1.3 .

[0119] The CoCrV provided in this comparative example 1.5 FeNiB 1.3 The preparation method of the alloy comprises the following steps:

[0120] (1) According to the target molar ratio of Co:Cr:V:Fe:Ni:B=1:1:1.5:1:1:1.3, the mass ratios of Co raw material, Cr raw material, V raw material, Fe raw material, Ni raw material and B raw material are converted to the nearest 0.001 g, and the Co raw material, Cr raw material, V raw material, Fe raw material, Ni raw material and B raw material with a purity of more than 99.99wt.% are weighed and mixed;

[0121] Before mixing, the Co raw material, the Cr raw material, the V raw material, the Fe raw material, the Ni raw material and the B raw material are respectively ultrasonically cleaned with anhydrous ethanol for 6 to 8 minutes, and the cleaned raw materials are placed in a drying box and dried at 200° C. for 30 minutes;

[0122] (2) The mixed material obtained in step (1) is placed in a medium frequency induction furnace for smelting. Before smelting, the medium frequency induction furnace is evacuated to a vacuum of 1 to 2×10 -3 Pa, then backwash argon to 0.06MPa, turn on the power, control the current during smelting to 420A, then heat up to 300℃, preheat for 5min, continue to increase the current after preheating and slowly heat up until the raw material is completely melted, keep warm for 10min, and pour into the crucible after melting evenly to cool and solidify, to obtain the CoCrV 1.5 FeNiB 1.3 High entropy alloy.

[0123] That is to say, referring to Example 3, the difference of this comparative example is only that the ratio of the V element in the high entropy alloy is increased, that is, x=1.5, and the ratio of the B element in the high entropy alloy is increased, that is, y=1.3.

[0124] The CoCrV prepared in this comparative example 1.5 FeNiB 1.3 The compressive stress-strain, hardness and strength test results of high entropy alloys are listed in Table 1.

[0125] Table 1:

[0126]

[0127] “ / ” in the table means no data.

[0128] From the attached figure and the data in Table 1, it can be seen that:

[0129] The CoCrV provided by the present invention x FeNiB y (0.1≤x≤1, 0.1≤y≤1) The high entropy alloy structure is composed of FCC phase and Cr2B phase, in which the Cr2B phase content is ≥9.9%. When metal element V and non-metal element B are added at the same time, Cr2B phase will appear in the alloy, and as the content of V element and B element increases, the content of Cr2B phase gradually increases.

[0130] The CoCrV provided by the present invention x FeNiB y(0.1≤x≤1, 0.1≤y≤1) The high entropy alloy has excellent comprehensive mechanical properties, with significantly improved hardness and strength. The hardness is ≥165.4HV, up to 476.6HV, the yield strength is ≥176.2Mpa, up to 501Mpa, and the tensile strength is ≥390MPa, up to 680Mpa. Moreover, with the increase of the content of V and B elements, the plastic strain decreases all the time, the microhardness and yield strength increase first, and the tensile strength increases first and then decreases.

[0131] The CoCrV provided by the present invention 0.5 FeNiB 0.3 High entropy alloys, CoCrV at 700℃ and 900℃ 0.5 FeNiB 0.3 The microstructure of the high entropy alloy has not changed and is still the FCC+Cr2B phase. The mechanical properties have not changed significantly, indicating that the alloy has good high temperature resistance.

[0132] In Comparative Examples 2, 3 and 4, after changing the element composition or element ratio of the high entropy alloy, the performance of each phase was significantly reduced. 0.3 Although the microhardness and tensile strength are improved, the plasticity is too poor and it is easy to break; CoCrV prepared in Comparative Example 3 0.5 Although FeNi has good plasticity, its microhardness, yield strength and tensile strength are too low; CoCrV prepared in Comparative Example 4 1.5 FeNiB 1.3 Although the microhardness and tensile strength are high, the plasticity is too poor and it is very easy to break. Therefore, by adopting the preferred high entropy alloy composition and atomic ratio of the present invention, through the synergistic effect of V element and B element, the hardness and strength properties can be coordinated to achieve the best effect, and at the same time, it has good high temperature resistance.

[0133] In summary, the present invention uses a base alloy composed of Co, Cr, Fe, and Ni with a molar ratio of 1:1:1:1, adds metal element V and non-metal element B for the first time, and further limits the stoichiometric ratio corresponding to V to 0.1≤x≤1, and the stoichiometric ratio corresponding to B to 0.1≤y≤1, so that the high entropy alloy described in the present application not only has good mechanical properties, excellent strength-plasticity matching and high strength, but also has good high-temperature stability, can meet the use requirements of power grid bolts, and can be used for the preparation of power grid bolt components.

[0134] The CoCrV provided by the present invention x FeNiB y(0.1≤x≤1, 0.1≤y≤1) High entropy alloy has excellent comprehensive mechanical properties, good plasticity, high hardness, strength and good high temperature resistance, can meet the use requirements of power grid bolts, and can be used for the preparation of power grid bolt components; the present invention adopts the medium frequency induction furnace smelting method to realize the preparation of new alloy ingots, and the structure is uniform and the performance is stable, wherein kilogram-level alloy ingots are prepared, and the preparation method is simple, practical, and easy to promote.

[0135] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A high-entropy alloy with strong plasticity and high temperature resistance, characterized in that: It is composed of Co, Cr, V, Fe, Ni and B, and the elemental composition is CoCrV x FeNiB y , where 0.1≤x≤1, 0.1≤y≤1.

2. The high-strength, high-temperature-resistant, high-entropy alloy according to claim 1, characterized in that: 0.1≤x≤0.5, 0.1≤y≤0.5; The high-strength plastic high-temperature resistant high-entropy alloy structure consists of an FCC phase and a Cr2B phase, wherein the content of the Cr2B phase is ≥9.9%; The strong plasticity high temperature resistant high entropy alloy has a tensile yield strength of ≥176.2 MPa, a tensile strength of ≥390 MPa, a tensile deformation rate of ≥1%, and a hardness of ≥165.4 HV.

3. A method for preparing a high-plasticity, high-temperature-resistant, high-entropy alloy as claimed in claim 1 or 2, characterized in that: include: (1) According to the target molar ratio, Co raw material, Cr raw material, V raw material, Fe raw material, Ni raw material and B raw material are weighed and mixed; (2) The mixed material obtained in step (1) is placed in a medium frequency induction furnace for smelting, and after being evenly melted, poured into a crucible for cooling and solidification.

4. The preparation method according to claim 3, characterized in that: The purity of the raw material in step (1) is ≥99.99wt%.

5. The preparation method according to claim 3, characterized in that: Before the mixing in step (1), the Co raw material, the Cr raw material, the V raw material, the Fe raw material, the Ni raw material and the B raw material are ultrasonically cleaned and dried respectively.

6. The preparation method according to claim 5, characterized in that: The solvent for ultrasonic cleaning is anhydrous ethanol, and the time for ultrasonic cleaning is 6 to 8 minutes.

7. The preparation method according to claim 3, characterized in that: In step (2), the medium frequency induction furnace is evacuated to 1-2×10 -3 Pa, then recoil argon to 0.06 ~ 0.08MPa, turn on the power, and then heat to 300 ℃, preheat for 5 ~ 8min, and then slowly heat until the raw material is completely melted after preheating, and keep warm for 10 ~ 15min.

8. The preparation method according to claim 7, characterized in that: In step (2), the smelting current is 400-600A.

9. A high-strength, high-ductility, high-temperature-resistant, high-entropy alloy as claimed in claim 1 or 2, applied to power grid bolts.

10. A high entropy alloy power grid bolt, made of the high-plasticity, high-temperature-resistant high entropy alloy according to claim 1 or 2.